Revealing the mechanism beneath the effects of starch-amino acids interactions on starch physicochemical properties by molecular dynamic simulations. (March 2022) - Xu, Huixian; Zhang, Shaobo; Yu, Wenwen
Abstract: In this study, the effects of different amino acids (AAs) including glycine (Gly), lysine (Lys) and glutamic acid (Glu) on starch physicochemical (gelatinization, swelling capacity, pasting and retrogradation) and morphological characteristics were investigated using differential scanning calorimeter, rapid visco analyser, a novel automatic segmentation methodology, along with both SEM and polarization microscope under normal and polarized light. Results showed that at a concentration of 3% ( w / w ), the addition of AAs showed no or only limited effects on starch granular morphological properties and crystallinity. Nevertheless, AAs could significantly inhibit starch granular swelling and gelatinization during heating, especially for charged AAs including Glu and Lys, leading to lower swelling capacity but higher gelatinization temperatures (p < 0.05). Moreover, the starch-AAs interactions also significantly decreased the starch viscosities including peak, trough, final and the setback viscosities, through retarding the leaching of starch molecules from inside. The molecular dynamics simulation further reveals that compared with water molecules, in an order of Glu > Lys > Gly, the interactions between AAs and water significantly decreased the number of starch-water hydrogen bonds, maintaining a higher number of starch-starch intra hydrogen bonds. This in turn improved the intra-hydrogen bonds within starch chains, resulting to more stable structures and thus inhibited starch gelatinization as well as its swell capacity. This study provides important information in terms of the application of different of AAs on starch aiming to improve starch physicochemical properties for better food processing and better starch functional properties. Graphical abstract: Image 1 Highlights: Amino acids have no significant effects on starch morphological properties. Effects on starch crystallinity depend on the crystallinity of amino acids. Amino acids inhibit starch swelling/gelatinization in an order of Glu > Lys > Gly. Amino acid-water interactions significantly decreased starch-water hydrogen bonds. Amino acid-water hydrogen bonds was in an order of Glu > Lys > Gly.